Coagulation Parameters in Elderly Patients with Severe Pneumonia: Correlation with Disease Severity and Prognosis - Zhang Q; Liu Y; Tong C; Zhang L; Li R; Guo W; Li J (Infection and Drug Resistance)
Qiuyue Zhang,1,* Yingchao Liu,1,* Chuntang Tong,2 Lina Zhang,3 Rongchen Li,1 Wenbin Guo,4 Jianliang Li5 1Department of Clinical Laboratory, The Second People’s Hospital of Liaocheng, Linqing, Shandong, 252600, People’s Republic of China; 2Department of Respiratory Medicine, The Second People’s Hospital of Liaocheng, Linqing, Shandong, 252600, People’s Republic of China; 3Department of Scientific Research Management Division, The Second People’s Hospital of Liaocheng, Linqing, Shandong, 252600, People’s Republic of China; 4Department of Intensive Care Unit, The Second People’s Hospital of Liaocheng, Linqing, Shandong, 252600, People’s Republic of China; 5Department of Thoracic Surgery, The Second People’s Hospital of Liaocheng, Linqing, Shandong, 252600, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianliang Li, Department of Thoracic Surgery The Second People’s Hospital of Liaocheng, 306 health Street, Linqing, Shandong, 252600, People’s Republic of China, Tel +86 15020622456, Email lijianliangl724@163.comObjective: This study aimed to investigate the levels of coagulation parameters in elderly patients with severe pneumonia and analyse their correlation with disease severity and prognosis.Methods: A retrospective study was conducted on 207 elderly patients (aged ≥ 60 years) with severe pneumonia admitted to our hospital between January 2022 and December 2023. Demographic data, clinical characteristics and coagulation parameters, including prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time and fibrinogen (FIB), were collected. Patients were divided into survivor and non-survivor groups based on 28-day mortality. The differences in coagulation parameters between groups and their correlation with disease severity and prognosis were analysed.Results: The 28-day mortality rate was 52.2%. Non-survivors had significantly higher PT, APTT and D-dimer levels and lower FIB levels than survivors (p < 0.05). Multivariate logistic regression analysis showed that elevated PT (odds ratio [OR] = 1.218, 95% confidence interval [CI]: 1.076– 1.379, p = 0.002) and D-dimer (OR = 1.109, 95% CI: 1.032– 1.192, p = 0.005) were independent risk factors for 28-day mortality. The combined model using PT and D-dimer showed the highest predictive value for 28-day mortality (area under the curve = 0.801, 95% CI: 0.739– 0.863, p < 0.001), with a sensitivity of 0.759 and specificity of 0.758.Conclusion: Coagulation dysfunction is common in elderly patients with severe pneumonia. Prothrombin time and D-dimer levels are closely associated with disease severity and can be valuable indicators for predicting prognosis in this population.Keywords: elderly, severe pneumonia, coagulation parameters, disease severity, prognosis